Makna Denotatif dan Konotatif pada Lirik Lagu “Saudade” Karya Kunto Aji - Dina Nopita; Desma Yuliadi Saputra; Rina Andriani (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the denotative and connotative meanings in the lyrics of Kunto Aji's song "Saudade." The approach used is descriptive qualitative with semantic methods to explore the meaning of language in detail. The data collected in this study are words, phrases, and sentences in the song lyrics that contain both meanings. Data collection techniques were carried out through observation and recording methods, while data analysis was carried out by grouping and understanding the meanings based on the context that appears in the lyrics. The results of the study show that the denotative meaning in the song tends to be direct and clear, while the connotative meaning is more often used to express complex emotions. The lyrics of the song "Saudade" describe feelings of longing, loss, and also deep reflections on life experiences. The use of connotative meanings strengthens the poetic and emotional elements, thus creating an emotional bond between the song and its listeners.